An alpha-helical hydrophobic hairpin as a specific determinant in protein-protein interaction occurring in Escherichia coli colicin A and B immunity systems. - Geli, V (1992)
A collection of chimeric pore-forming domains between colicins A and B was constructed to investigate the specific determinants responsible for recognition by the corresponding immunity proteins. The fusion sites in the hybrid proteins were positioned according to the three-dimensional structure of the soluble form of the colicin A pore-forming domain. The hydrophobic hairpin of colicin pore-forming domains, buried in the core of the soluble structure, was the main determinant recognized by the integral immunity proteins. The immunity protein function may require helix-helix recognition within the lipid bilayer.